Rosalía’s Lux (2025): A Transmedia Analysis of the Album Launch and Post-digital Music Marketing - Pérez-Rufi, José Patricio (Universidad de Málaga, 2025)
This paper focuses on the post-digital, transmedia marketing campaign surrounding Rosalía’s 2025 album Lux. It examines how a succession of communicative actions —from urban and digital teasers to listening parties and media appearances— built a coherent brand identity that went beyond the music itself. The aims are to identify the main strategies for visibility and community building, to explore the interplay between visual design, symbolic narrative and audience participation, and to assess the public reception of the release. A qualitative, interpretive methodology is employed, framed as an instrumental case study, using a corpus that includes visual materials, live events, social-media posts and journalistic articles. Key findings include the deployment of religious iconography on the visual identity of Rosalia’s Lux project, the release of the single “Berghain” with high-profile collaborators, listening parties in Mexico City, New York and Barcelona, the management of an album leak prior to the official launch, and the performance of “Reliquia” at the Los40 Music Awards. The conclusions affirm that the campaign represents a paradigmatic example of contemporary music marketing, successfully combining tradition and modernity, exclusivity and participation, and consolidating Rosalía’s status as a global cultural figure.
Lux de Rosalía (2025): análisis transmedia del lanzamiento del álbum y marketing musical posdigital
El objeto de estudio es la campaña de marketing posdigital y transmedia desplegada en torno al álbum Lux de Rosalía (2025). Se analiza cómo las acciones comunicativas —desde anuncios urbanos y digitales hasta fiestas de escucha y apariciones en medios— construyeron una identidad de marca coherente que trascendió la dimensión musical. Los objetivos planteados son identificar las principales estrategias de visibilidad y comunidad, examinar la articulación entre diseño visual, narrativa simbólica y participación del público y valorar la recepción social del lanzamiento. La metodología adoptada es de carácter cualitativo e interpretativo, basada en un estudio de caso instrumental, con un corpus compuesto por materiales visuales, eventos presenciales, publicaciones en redes y artículos periodísticos. Entre los resultados destaca el uso de iconografía religiosa en los teasers de la identidad visual del proyecto Lux de Rosalía, el estreno del single “Berghain” con colaboradores de prestigio, la organización de fiestas de escucha en México, Nueva York o Barcelona, la gestión de la filtración previa al lanzamiento oficial y la presentación del tema “Reliquia” en los premios Los40. Las conclusiones confirman que la campaña constituyó un ejemplo paradigmático de marketing musical contemporáneo, capaz de combinar tradición y vanguardia, exclusividad y participación y de consolidar a Rosalía como una figura de alcance global.
Keywords: Rosalía (1993-) - Crítica e interpretación; Industria cultural - Marketing; Grabaciones sonoras - Industria; Industria discográfica; Marketing cultural; Medios de comunicación de masas; Música popular; Identidad cultural